Fabrication Of Ipmc Biomimetic Flapping Thruster And Its Speed Control Based On Nafion Membrane - Rosly, Muhammad Aliff (2016)
The increasing need for real preliminary information verification in small space for any underwater operations involving search and rescue, archaeological exploration and oceanographic studies had inspired the development of biomimetic underwater flapping thruster using Ionic Polymer Metal Composite (IPMC) smart actuator. However, one of the problems with this kind of thruster is the inconsistent and uncontrollable thrust generation due to no proposed control mechanism. Therefore, the main objective of this research is to equip this biomimetic flapping thruster with speed control system to ensure the motion of this thruster is following the pre-determined speed. Firstly, the fabricated IPMC actuator’s actuation and controllability were verified. MATLAB/Simulink and ArduinoIDE/PLX-DAQ interfaces were utilized as control and data logging configurations to develop control system using Arduino micro controller. Results analysis of IPMC actuator deflection response from laser sensor feedback proves that the fabricated IPMC actuator managed to track step, square wave, and sinusoidal wave input signal. Hence, it is capable of producing a flapping actuation that was needed in a fish like thruster. Then the IPMC actuator was utilized as the thruster's caudal fin to move the thruster body at certain speed. An Inertial Measurement Unit (IMU) device was used as the speed and orientation sensor for open loop and closed loop control experiments. Open loop results prove that the generated thruster instantaneous speed increases with the increases of amplitude of voltage to IPMC. Based on this information, a closed loop control system was developed, and its performance was verified. By controlling the voltage amplitude, the closed loop control system managed to control thruster’s instantaneous speed around the 1.5 cm/s setpoint. In conclusion, the speed of IPMC based flapping thruster can be effectively controlled by using IMU device as a speed feedback. This research knowledge is critical in providing other IPMC based biomimetic robot researcher a solution for controlling the thrust generation.